Analisis Penerapan Manajemen Perubahan: Studi Kasus Pada UMKM Mie Uda Bro, Lubuk Begalung, Padang. - Amanda Putri Rahayu; Dinda Alya; Maharani Gabriella Rifera; Ramdani Bayu Putra; Zulfajri Zulfajri (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
This study aims to examine the impact of implementing various changes implemented by the company on employees of the MSME "Mie Uda Bro" Padang City, West Sumatra. This activity aims to analyze and understand changes in strategy at Mie Uda Bro MSMEs, Lubuk Begalung, Padang. The focus of this activity is on consumer behavior and business competition, which are considered key factors in increasing company effectiveness and maintaining competitiveness. A case study approach was used in this activity, involving in-depth interview methods, direct observation and document analysis to obtain a comprehensive picture of the internal dynamics and challenges faced by MSMEs (Micro, Small and Medium Enterprises) at Mie Uda Bro. The research results show that positive employee behavior and the implementation of strategic changes play a significant role in increasing company effectiveness. It is hoped that this Social Service activity will have an impact on increasing the insight, skills and understanding of business owners to face similar challenges and increase their competitiveness in an increasingly competitive market.